Ретроспективний аналіз комбінованого лікування хворих на рак шийки матки: шляхи оптимізації лікувальних програм - Вінницька, А.Б. (Онкологія, 2002)
Резюме. Проаналізовано ефективність лікування (5-річна виживаність та тривалість безрецидивного періоду) 369 хворих на рак шийки матки (РШМ) в Інституті онкології АМН України залежно від стадії захворювання, ураження регіонарних лімфатичних вузлів, методів комбінованого лікування. Встановлено доцільність включення неоад’ювантної хіміопроменевої терапії (НАТ) в схеми комбінованого лікування хворих на РШМ стадій Т1АВN0M0, T1BN1M0, Т2N0M0, Т2N1M0. При ураженні регіонарних лімфатичних вузлів найбільш ефективним виявилось поєднання НАТ та ад’ювантного лікування.

Ключевые слова: рак шийки матки, комбіноване лікування, неоад’ювантна терапія, ад’ювантна терапія, ефективність. Summary. The paper analyses the efficacy of treatment (5-year survival and duration of relapse-free period) of 369 patients with uterine neck cancer (UNC) treated in the Institute of Oncology of the Ukrainian Academy of Medical Sciences, depending on the stage of disease, involvement of regional lymph nodes, and schedule of the combined treatment. It is found that application of neoadjuvant chemoradiotherapy in a combined treatment of UNC patients at stages Т1АВN0M0, T1BN1M0, Т2N0M0, Т2N1M0. In UNC patients with metastatic affection of regional lymph nodes, the most efficient was the combination of neo- and adjuvant therapies.

Key Words: uterine neck cancer combined treatment, neoadjuvant therapy, adjuvant therapy, efficacy.